LEGAL ASPECTS OF THE LEGAL STATUS OF COMPANIES OR BUSINESS ENTITIES IN BUSINESS ACTIVITIES - Rahmawati Hutagalung (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Companies are always connected with third parties and want to protect honestly run companies ("te goeder trouw"), then it is very important the meaning of the legality of a company in business activities. Legality of a company or business entity is the most important element, because the legality is the identity of a legal or legalized a business entity so recognized by the community. Company legality must be legitimate according to the laws and regulations, in which the company is protected or protected by various documents until it is lawful. Forms of Corporate Legality There are several types of identity that legalize business entities, including: company name, corporate brand, and trading business license. While the benefits of the legality of the company is as a means of legal protection, means of promotion, evidence of compliance with the law, facilitate a project and facilitate business development. The number of companies established without legalizing the company, is very detrimental to other companies that carry out their business activities honestly.